2021
DOI: 10.4018/jgim.294905
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Human Interactive Accounting Management Information Systems Based on Artificial Intelligence

Abstract: BACKGROUND: With the gradual improvement of market economy, people' s consumption level is constantly improving, and the quality requirements are getting higher and higher. OBJECTIVES: In order to study the management accounting information analysis platform based on Artificial Intelligence (AI) and realize the goal of accounting computerization, the application of AI in expert system is applied to the field of accounting information analysis. METHODS: The combination of subsystems is applied to the constructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…e accounting entries under the corresponding economic business activities and accounting standards are obtained through the continuous feedback training of the neural network [18,19]. the output of each node of the input layer is calculated as given by the following equation:…”
Section: E Bp Ann Modelmentioning
confidence: 99%
“…e accounting entries under the corresponding economic business activities and accounting standards are obtained through the continuous feedback training of the neural network [18,19]. the output of each node of the input layer is calculated as given by the following equation:…”
Section: E Bp Ann Modelmentioning
confidence: 99%
“…Therefore, to explore the strategic role of dynamic AIS capability, this study investigates the relationship between dynamic AIS capability and business-process capabilities. In addition, a number of studies have demonstrated the positive effects of information systems capability on overall organizational performance [28][29][30][31], but our understanding of the business processes capabilities through which such gains are achieved remains limited due to a lack of focus on the turbulent business environment.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have applied AI techniques to the accounting and finance fields, significantly improving business processes. Optical character recognition [13], intelligent accounting information systems [14], and intelligent trading systems [15] are widely employed in practice, enhancing business processing efficiency. AI techniques enable feature extraction from existing data, as reported in numerous studies.…”
Section: B Related Workmentioning
confidence: 99%